THE ATTITUDE OF UZBEK SCIENTISTS TO THE PROBLEM OF DEVELOPING THE PERCEPTION AND IMAGINATION OF VISUAL ART WORKS AMONG SCHOOLCHILDREN (Web of Teachers: Inderscience Research, 2024)
This article discusses the attitude of Uzbek scientists to the problem of developing the perception and imagination of visual art works among schoolchildren.